SOCIAL MEDIA-DRIVEN CONSUMER BOYCOTT IN INDONESIA: EXPLORING THE INTENSION-BEHAVIOR GAP THROUGH SOCIAL INFLUENCE AND ISLAMIC ETHICS - Lutfiyah Rahma Novelika; Maryam Bte Badrul Munir; Moh. Farih Fahmi (Referensi Islamika: Jurnal Studi Islam, 2026)
This study systematically synthesizes existing literature to explain how social media-driven social influence shapes consumer boycott intention, what factors contribute to the intention–behavior gap between boycott intention and actual participation, and how Islamic ethical values explain consumer participation in social media-driven boycott movements in Indonesia. A Systematic Literature Review (SLR) was conducted using the PRISMA framework to identify, screen, and select relevant studies. Twenty-eight articles published between 2018 and 2026 met the predefined inclusion and exclusion criteria and were analyzed using thematic synthesis to identify recurring themes, compare findings across studies, and develop an integrated understanding of consumer boycott movements. Social media consistently strengthens consumer boycott intention by accelerating information dissemination, reinforcing collective awareness, and amplifying social influence. However, stronger boycott intention does not necessarily translate into actual boycott participation because consumer behavior is simultaneously shaped by psychological, contextual, and practical factors, including moral reasoning, perceived boycott effectiveness, product availability, and brand attachment. The synthesis also indicates that Islamic ethical values, reflected in religiosity, humanitarian solidarity, and principles of justice, provide an important framework for explaining consumer participation and sustained commitment to boycott movements among Indonesian Muslim consumers. Integrating digital social influence, the intention–behavior gap, and Islamic ethical values provides a more comprehensive understanding of consumer boycott behavior in digital environments. The findings may support future research on ethical consumption while offering insights for policymakers and businesses in responding to consumer activism surrounding socio-political issues. This review contributes by synthesizing evidence across studies into three interconnected themes social media-driven social influence, the intention–behavior gap, and Islamic ethical values thereby providing a more comprehensive understanding of consumer boycott movements in Indonesia.